CUSTOMER SATISFACTION AS A MEDIATOR: THE IMPACT OF PRODUCT QUALITY AND SERVICE QUALITY ON REPURCHASE INTEREST - Bekti Ismiah; Sutianingsih (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
Vegetables are rich in vitamins, minerals, and fibre. Thus, fresh veggies appeal to more individuals. This study examines how product and service quality affects repurchase intentions through consumer satisfaction. Bekti Mundakir Fresh Vegetables in Selo Boyolali will host the study. This study employs a questionnaire for quantitative research. Data from 90 individuals will be collected using questionnaires. Using SPSS 25, this study will examine validity, reliability, multiple regression, and Sobel test. This study shows that product quality does not affect repurchase intention. However, service quality and customer satisfaction affect repurchase intention. Customer happiness depends on product and service quality. Customer satisfaction may moderate product and service quality on repurchase intention. Keywords: product quality, service quality, consumer satisfaction, repurchase interest